Jet production in polarized deep inelastic scattering at next-to-next-to-leading order - Borsa Sanjuán, Ignacio (2020)
We present the next-to-next-to-leading order (NNLO) calculation for single-inclusive jet production in polarized deep inelastic lepton-nucleon scattering e→p→→jet+X. We perform the computation based on the projection-to-Born method by combining our recent next-to-leading order result for di-jet production in polarized deep inelastic lepton-nucleon scattering along with the NNLO coefficients for the inclusive cross section. In this way, we achieve NNLO accuracy in a fully exclusive way for single-jet observables, the first time for a polarized cross section. We study the perturbative stability and phenomenological consequences of the QCD corrections for Electron-Ion Collider kinematics.